1999
DOI: 10.1038/44611
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of cyclin B1 requires E2F and cyclin-A-dependent rearrangement of the anaphase-promoting complex

Abstract: In mammalian somatic-cell cycles, progression through the G1-phase restriction point and initiation of DNA replication are controlled by the ability of the retinoblastoma tumour-suppressor protein (pRb) family to regulate the E2F/DP transcription factors. Continuing transcription of E2F target genes beyond the G1/S transition is required for coordinating S-phase progression with cell division, a process driven by cyclin-B-dependent kinase and anaphase-promoting complex (APC)-mediated proteolysis. How E2F-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
285
7
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(312 citation statements)
references
References 28 publications
15
285
7
5
Order By: Relevance
“…More importantly, we further demonstrated that ectopic expression of cyclin E led to an increase in the phosphorylation of endogenous Cdh1 ( Figure 4H), whereas depletion of cyclin E resulted in a sharp decrease in endogenous Cdh1 phosphorylation ( Figure 4I). Therefore, consistent with previous reports [25,44,45], these results support a model that the Fbw7/cyclin E signaling pathway potentially regulates the E3 ligase activity of APC Cdh1 by affecting the interaction of Cdh1 with the APC core subunit primarily through regulating Cdh1 phosphorylation status ( Figure 6). …”
Section: Cdk2/cyclin E Directly Phosphorylates Cdh1 At Multiple Sitessupporting
confidence: 81%
See 1 more Smart Citation
“…More importantly, we further demonstrated that ectopic expression of cyclin E led to an increase in the phosphorylation of endogenous Cdh1 ( Figure 4H), whereas depletion of cyclin E resulted in a sharp decrease in endogenous Cdh1 phosphorylation ( Figure 4I). Therefore, consistent with previous reports [25,44,45], these results support a model that the Fbw7/cyclin E signaling pathway potentially regulates the E3 ligase activity of APC Cdh1 by affecting the interaction of Cdh1 with the APC core subunit primarily through regulating Cdh1 phosphorylation status ( Figure 6). …”
Section: Cdk2/cyclin E Directly Phosphorylates Cdh1 At Multiple Sitessupporting
confidence: 81%
“…It was previously reported that phosphorylation of Cdh1 by Cdk2/cyclin A at multiple sites (S40, T121, S151 and S163) located at the N terminus of Cdh1 could lead to the dissociation of Cdh1 from the APC/C core subunit, thus terminating the E3 ligase activity of APC Cdh1 before S phase entry [44]. Later work by Keck et al [25] expanded this finding by demonstrating that Cdk2/cyclin E could also phosphorylate Cdh1 to inactivate Cdh1.…”
Section: Cdk2/cyclin E Directly Phosphorylates Cdh1 At Multiple Sitesmentioning
confidence: 79%
“…ak, J.J. Tyson / Journal of Theoretical Biology 230 (2004) 563-579At Start, Cdh1 must be inactivated so that mitotic cyclins may reappear. In budding yeast, this is the job of Clb5/Cdc28 (Shirayama et al, 1999), and in mammalian cells, of CycA/Cdk2 (Lukas et al, 1999). More on this shortly.…”
Section: Article In Pressmentioning
confidence: 98%
“…Cyclin A/cdk2 appears to be involved in the activation (Furuno et al, 1999;Mitra and Enders, 2004), and possibly the stabilization of cyclin B, the latter by indirectly inhibiting the anaphase-promoting complex/cyclosome (APC/C) (Lukas et al, 1999). Cyclin A is itself destroyed by the APC/C at prometaphase (den Elzen and Pines, 2001) inferring that its activity is required until that time.…”
Section: Introductionmentioning
confidence: 99%